A quantitative determination of lipid bilayer deposition efficiency using AFM. Issue 32 (2nd June 2021) - Wood, Mary H.; Milan, David C.; Nichols, Richard J.; Casford, Michael T. L.; Horswell, Sarah L.
Abstract : The efficacy of different methods for depositing a DMPC or mixed DMPC–cholesterol (3 : 1) lipid bilayer onto a silicon substrate has been investigated in a quantitative manner using atomic force microscopy image analysis to extract surface coverage. Abstract : The efficacy of a number of different methods for depositing a dimyristoylphosphatidylcholine (DMPC) lipid bilayer or DMPC–cholesterol (3 : 1) mixed bilayer onto a silicon substrate has been investigated in a quantitative manner using atomic force microscopy (AFM) image analysis to extract surface coverage. Complementary AFM-IR measurements were used to confirm the presence of the lipids. For the Langmuir–Blodgett/Schaefer deposition method at temperatures below the chain-melting transition temperature ( T m ), a large number of bilayer defects resulted when DMPC was deposited from a water subphase. Addition of calcium ions to the trough led to smaller, more frequent defects, whereas addition of cholesterol to the lipid mixture led to a vast improvement in bilayer coverage. Poor coverage was achieved for deposition at temperatures above T m . Formation of the deposited bilayer from vesicle fusion proved a more reliable method for all systems, with formation of near-complete bilayers within 60 seconds at temperatures above T m, although this method led to a higher probability of multilayer formation and rougher bilayer surfaces.